If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(u + -8) = 3(u + -8) Reorder the terms: 7(-8 + u) = 3(u + -8) (-8 * 7 + u * 7) = 3(u + -8) (-56 + 7u) = 3(u + -8) Reorder the terms: -56 + 7u = 3(-8 + u) -56 + 7u = (-8 * 3 + u * 3) -56 + 7u = (-24 + 3u) Solving -56 + 7u = -24 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. -56 + 7u + -3u = -24 + 3u + -3u Combine like terms: 7u + -3u = 4u -56 + 4u = -24 + 3u + -3u Combine like terms: 3u + -3u = 0 -56 + 4u = -24 + 0 -56 + 4u = -24 Add '56' to each side of the equation. -56 + 56 + 4u = -24 + 56 Combine like terms: -56 + 56 = 0 0 + 4u = -24 + 56 4u = -24 + 56 Combine like terms: -24 + 56 = 32 4u = 32 Divide each side by '4'. u = 8 Simplifying u = 8
| 18w+6k= | | x+.03x=1546.03 | | 0.12x=1 | | 2=y+5 | | x*0.15=1 | | c-9= | | x+.03=1546.03 | | 19+4m=4m+11 | | x*1=0.15 | | 3(x+1)=3+2x+7 | | 6x+2y=-26 | | 6x-3-8x=7 | | 3m+5=6m-4 | | 12cosx=-7 | | -2.6x+18=-2.4x+22 | | G(x)=4x-12x+8 | | 7a^2-9ab+8a=0 | | ax-5cx+4ay-20cy=0 | | -4-x=15 | | G(x)=(4x-12x)+8 | | ax-8a+7x-56=0 | | x+x-5+2x=115 | | x^2-2xy+y^2= | | 6x^3y^3-12x^2y^3+6xy^3=0 | | v=1/3(5.5)(15) | | 1x=-55 | | 3xyz^2-9xyz-12xy=0 | | 1x=-5 | | -20+x=19-4x | | 4x=3x+19 | | 4x^3+4x^2-48x=0 | | 9x^2-5x+2=0 |